(untitled) - Knox, Paul L. (Upper Saddle River, NJ., 2003)
The Updated Second Edition contains materials about recent world events triggered by the September 11th attacks on New York City and Washington D.C. Provides numerous topics, including Mapping Cultural Identities, Nature, Society, and Technology, The Politics of Territory and Space. The Updated Second Edition contains new materials that address the actual world events triggered by the attacks on the United States. For professionals in the field of geography.
Keywords: Human geography,Địa lý con người